A STUDY ON APPLICATION ZINC OXIDE (ZNO) NANOPARTICLES AS SECURITY INK FOR VALUABLE DOCUMENTS - Widhya Budiawan; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Pusbindiklat - LIPI, 2012)
Ink made from zinc oxide (ZnO) nanoparticles colloid has been synthesized by using a sol-gel method. Employing an XRD, it was obtained that the sizes of particles were around 3–4 nm. Utilizing a UV-Vis spectrometer, it was found that the band gap energies were 3.5 and 3.45 eV for the sizes of 3 and 4 nm, respectively. For the purpose of testing the ink effectiveness, the ZnO colloid was mixed with polyethylene glycol (PEG) 400 or glycerine. Using pure ZnO colloid as printer ink, invisible characters under natural illumination had been successfully printed on specific papers. Under ultraviolet (UV) illumination, the invisible characters became visible. The developed ink, therefore, has potential applications for security of bank notes or passbooks.